Transpersonal Psychology and Science An Evaluation of Its Present Status and Future Directions. - MacDonald, Douglas A.; Almendro, Manuel (Newcastle-upon-Tyne : Cambridge Scholars Publisher, 2021)
Founded in the 1960s, transpersonal psychology is a subdiscipline of psychology that has been dedicated to the study of exceptional human experiences and functioning inclusive of ancient and indigenous spiritual and mystical traditions. While initially holding tremendous promise to expand psychological science and practice beyond the purview of conventional psychology, the field has encountered a variety of challenges that its advocates have recognized as compromising its progress. Among the most pervasive of these challenges has been controversy and disagreement regarding the place of science.
Chapter Twenty-Seven -- Chapter Twenty-Eight -- Chapter Twenty-Nine -- References
Description based upon print version of record.
Includes bibliographical references.
eBooks on EBSCOhost
Keywords: Transpersonal psychology; Science and psychology; Psychologie transpersonnelle; Sciences et psychologie; Psychology; Science: general issues; Philosophy of science; Science and psychology; Transpersonal psychology